Effect of bath temperature on PbSe thin films prepared by chemical synthesis. (December 2015) - Anwar, Sharmistha; Anwar, Shahid; Mishra, Barada Kanta
Abstract: Lead selenide (PbSe) thin films were deposited using chemical bath deposition techniques by varying bath temperatures (70–90 °C) keeping deposition time and other parameters constant. The influence of the synthesis/bath temperature on structural and thermoelectric properties of as-deposited PbSe nanostructured film was investigated using x-ray diffraction, scanning electron microscope, Raman spectroscopy and thermo-emf measurement. The improvement of crystallinity of the PbSe films was studied using x-ray diffraction and Raman scattering. The structural parameters, such as the lattice constant ( a ), crystallite size ( D ), dislocation density ( δ ) and microstrain ( ε ) were evaluated from XRD spectra. The average crystallite size, as calculated from Scherrer's formula, increased from 22.45 to 24.87 nm as the bath temperatures was varied from 70 °C to 90 °C. The dislocation density and microstrain were found to vary inversely with the crystallite size, whereas the lattice constant was found to slightly different with an increase in crystallite size. The scanning electron microscopy observation shows that with an increase in bath temperature, the grain size increases and they agglomerates. At the elevated bath temperatures individual particles agglomerate and lead to higher grain density and film crystallinity. The thermo-emf measurements have shown n-type conductivity in the as deposited films.